Prevalence and risk factors of musculoskeletal disorder (MSD) among school teachers in Klang Valley / Tengku Farhanah Tengku Johari - Tengku Farhanah, Tengku Johari (2019)
Musculoskeletal disorder (MSD) is commonly suffered by most workers. Many studies had been done internationally to investigate its prevalence amongst teachers. However, there are still not much study done in Malaysia. The objective of this study is to investigate the prevalence and risk factors for MSD in teachers and to evaluate its association to individual and occupational characteristics. A cross-sectional study was done on 79 respondents from two schools in Klang Valley. One is a primary school and the other is a secondary school. A questionnaire was distributed to get their demographic and occupational information. The prevalence of MSD for the past 12 months was assessed using the Standardized Nordic Questionnaire (SNQ). The body part with the highest prevalence of pain was the neck (70.89%), followed by the shoulders (58.23%) and the low back area (49.37%). Some of the risk factors identified was prolonged standing and sitting, high stress, long working hours, not taking breaks during class, years of working and age. Significant association between these risk factors and the prevalence of MSD was verified (P < 0.05). The teachers need to be exposed to the preventive and management strategies such as taking breaks in between classes, staying in a proper working posture and reducing repetitive movement.